Common Interior Alaska Cryptogams : Fungi, Lichenicolous Fungi, Lichenized Fungi, Slime Molds, Mosses, and Liverworts - Laursen, Gary A. (Book collections on Project MUSE., 2009)
With Common Interior Alaska Cryptogams, Gary A. Laursen and Rodney Seppelt offer the first field guide to cryptogams of the Denali National Park and Preserve. Useful to both lay and professional investigators, this fully illustrated compendium covers mushroom fungi, lichenized fungi, lichenicolous fungi, slime molds, mosses, and liverworts. This field guide to commonly seen cryptogams will provide a basis for understanding their vast diversity of taxa, speciation, edibility, relative abundance, and utility, as well as the ecological roles played by these organisms.